Pseudosperma parvisporum sp. nov., (Inocybaceae, Basidiomycota) from Pakistan - Abbas, Ali; Naseer, Arooj; Khalid, Abdul Nasir (Phytotaxa, 2025)
A new species Pseudosperma parvisporum is described and illustrated here, based on morpho-anatomical and molecular phylogenetic characterization. The taxon is characterized by campanulate to becoming plano-convex to convex pileus at maturity, having 3.4–4.5 cm diam., with brown umbo, brownish golden to yellow fibrils spread on; up to 8 cm stipe, hollow, cylindrical and containing longitudinal striations on it; smaller basidiospores (8.86–10.86 × 5.06–6.2 μm); oblong to utriform, appeared in cluster cheilocystidia having 34.3–51.5 × 9.6–14.6 μm size and occurrence of fusiform to lageniform caulocystidia measuring 38.7 × 9.7 μm. In addition to these, the combined nrITS and nrLSU based phylogenetic analysis was done which supports its unique position and confirms it a new species as it forms a separate clade. The photographs, drawings and comparison with similar taxa are also provided here.